Engagement in a pilot produce prescription program in rural and urban counties in the Southeast United States - Owens, Caroline E.; Cook, Miranda; Reasoner, Tammy; McLean, Aleta; Webb Girard, Amy (Frontiers in Public Health, 2024)
In the United States, over one in every ten households experiences food insecurity. Food insecurity is associated with often co-occurring adverse health consequences, including risk for obesity, type 2 diabetes, and hypertension. Within the "Food is Medicine" intervention space, Produce Prescription Programs (PRx) seek to alleviate food insecurity and improve diet and health outcomes by leveraging access to produce through healthcare organizations. Though these programs are burgeoning across the United States, research surrounding their implementation and outreach is limited. This study outlines the implementation of one such program piloted in two regions of Georgia (US) between 2020-2022. We examine participants' baseline demographics, food security status, dietary patterns, and predictors of loss to follow-up. Specifically, this study focuses on whether those enrolled matched the target recipients (those living with food insecurity) and assesses potential retention factors. In the initial pilot period of this program, 170 participants enrolled across two sites in rural Georgia and one in a major metropolitan city. Of those enrolled, 100 individuals (59%) remained engaged for the entire six-month duration of programming. While many individuals met the target criteria of living with or at-risk of food insecurity, not all enrolled were living with low or very low food security. Odds of loss to follow-up were significantly greater among males compared to females and in metropolitan compared to rural cohorts. However, no other significant demographic or household composition differences were observed between those who completed the program and those who were lost to follow-up. This intervention study illustrates the potential of Produce Prescription programs to advance food and nutrition security and cardiometabolic health in rural and metropolitan areas across the United States. We conclude by discussing future research priorities in the context of Produce Prescription programs.